Murray's basic medical microbiology - Murray, Patrick R. (Philadelphia : Elsevier, 2023)
Provides complete coverage of the most commonly observed organisms and diseases, numerous case studies, review questions, and up-to-date content throughout, including coverage of COVID-19. Features a logical organization by organism, focusing on the association between an organism and disease. Provides over 180 clinical cases to strengthen understanding of infectious organisms in a clinical setting. Includes a brand new section with devoted chapters on diseases affecting each body system and the multiple organisms that may be responsible to help sharpen clinical reasoning skills. Includes differential diagnosis, organism classification overview, and a list of antimicrobials used to treat infections in the introductory chapter of each organism section, reinforcing clinical application and relevance. Contains numerous tables and high-quality illustrations that offer visual guidance and an easy review of key material. Includes more multiple-choice review questions to aid in self-assessment and examination preparation
Overview of medical microbiology -- Introduction to bacteria -- Aerobic gram-positive cocci -- Aerobic gram-positive rods -- Acid-fast bacteria -- Aerobic gram-negative cocci and coccobacilli -- Aerobic fermentative gram-negative rods -- Aerobic nonfermentative gram-negative rods -- Anaerobic bacteria -- Spiral-shaped bacteria -- Intracellular bacteria -- Introduction to viruses -- Human immunodeficiency viruses -- Human herpesviruses -- Respiratory viruses -- Hepatitis viruses -- Gastrointestinal viruses -- Human papillomavirus -- Introduction to fungi -- Cutaneous and subcutaneous fungi -- Systemic dimorphic fungi -- Opportunistic fungi -- Introduction to parasites -- Protozoa -- Nematodes -- Trematodes -- Cestodes -- Arthropods -- Upper respiratory tract infections -- Lower respiratory tract infections -- Gastrointestinal tract infections -- Genitourinary tract infections -- Central nervous system infections -- Skin and soft tissue infections -- Sepsis and cardiovascular infections -- Miscellaneous infections.
Includes index.
Keywords: Microbiology; Microbiological Phenomena; Case Reports; Examination Questions